2006
DOI: 10.1074/jbc.m603414200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Epidermal Growth Factor Receptor and Hypoxia-inducible Factor-1α Signal Pathways Increases Resistance to Apoptosis by Up-regulating Survivin Gene Expression

Abstract: Although increasing evidence supports a link between epidermal growth factor receptor (EGFR) signaling and resistance to apoptosis, the mechanism by which the EGFR signaling pathway inhibits apoptosis is not well understood. In this study, we found that epidermal growth factor ( The EGFR 2 signaling pathway plays a key role in the regulation of cell proliferation, survival, and differentiation (1, 2). It has been shown that the level of EGFR is up-regulated in many human tumor tissues. Activation of EGFR signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
208
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(228 citation statements)
references
References 35 publications
(53 reference statements)
14
208
2
1
Order By: Relevance
“…In addition, cell survival and cell death are both regulated by hypoxia, in part through the regulation of programmed cell death I and II processes named apoptosis and autophagy respectively. The regulation of apoptosis by hypoxia involves the regulation of the expression of genes such as Bid, Bax, Noxa, Survivin and Mcl-1 [5][6][7][8]. In addition, hypoxia selects cancer cells with reduced apoptotic potential [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cell survival and cell death are both regulated by hypoxia, in part through the regulation of programmed cell death I and II processes named apoptosis and autophagy respectively. The regulation of apoptosis by hypoxia involves the regulation of the expression of genes such as Bid, Bax, Noxa, Survivin and Mcl-1 [5][6][7][8]. In addition, hypoxia selects cancer cells with reduced apoptotic potential [9].…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation induces the expression of HIF‐1α, while the latter in turn causes radioresistance by triggering several signaling pathways. HIF‐1α inhibited the apoptosis of malignant cells,45, 46 induced γH2AX expression and hypoxic condition, enhanced DNA repair and finally led to the poor response of tumor treatment 47…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ueda et al 45 demonstrated that hypoxia under serum-starved conditions lead to increased survivin expression in human brain microvascular endothelial cells and EGF stimulation in breast cancer cell lines resulted in an upregulation of survivin. 46 This was caused by direct binding and activation of the survivin promoter by the hypoxia-inducible factor (Hif-1a). 46 In this line, knockdown of Hif-1a inhibited the expression of survivin in a pancreatic cancer cell line under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…46 This was caused by direct binding and activation of the survivin promoter by the hypoxia-inducible factor (Hif-1a). 46 In this line, knockdown of Hif-1a inhibited the expression of survivin in a pancreatic cancer cell line under hypoxic conditions. 47 In contrast, hypoxia or reoxygenation activated the PI3K/Akt pathway and lead to an upregulation of XIAP but not of survivin in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%